The central limit theorem for the sums of the discrete renewal processes - Kaminskienė, B. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Каминскене. Центральная предельная теорема для сумм дискретных процессов восстановленияB. Kaminskienė. Centrinė ribinė teorema diskretinių atstatymo procesų sumoms